Stereoselective reactions of arene chromium tricarbonyl complexes - Goodfellow, C (1989)
﻿ This thesis describes the application of (arene)Cr(CO)3 methodology to the Stereoselective and enantioselective synthesis of substituted arenes. Chapter one reviews the main methods of preparation and decomplexation of (arene)Cr(CO)3 complexes and the electronic and steric influences of the Cr(CO)3 unit on the arene. Chapter two demonstrates that the benzylic oxygen directing effect in complexation reactions operates via a direct oxygen bond to the incoming metal unit. Attachment of bulky ft-acceptor groups, such as t-butyldimethylsilyl, to the benzylic oxygen overrides this directing effect. Chapter three describes the regioselective Cl functionalisation of the cryptopine skeleton. Complexation of dihydrocrytopine gives only a single product, the relative configuration of the product being determined using an X-ray crystal structure analysis. Subsequent alkylation of the O-methyl derivative gives Cl alkylated products. Chapter four describes the regioselective ortho functionalisation of ephedrine and pseudoephedrine derivatives. Treatment of (1S,2R)-(N,O-dimethylpseudoephedrine) Cr(CO)3 with n-butyllithium leads to exclusive removal of the pro-(R) ortho proton. The observed stereoselectivity arises via Chapter five describes the regioselective C4 and C5 functionalisation of (hydrocotarnine)Cr(CO)3. Complexation of 1-methylhydrocotarnine occurs to give exclusively the exo-1-methyl derivative. Further functionalisation to give the 1,5- and 4,5-dimethyl products is also described. Chapter six describes the synthesis of ortho substituted (benzaldehyde)Cr(CO)3 complexes. Chiral material is available via preferential kinetic hydrolysis of, or classical separation of, the L-valinol derived imines. Chapter seven describes the Stereoselective addition of nucleophiles to (o-anisaldehyde) Cr(CO)3 and (o-trialkylsilylbenzaldehyde)Cr(CO)3. With (o-anisaldehyde)- Cr(CO)3 the additions are completely stereoselective giving the (RR,SS) diastereoisomer. With (o-trialkylsilylbenzaldehyde)Cr(CO)3 the ratio of products is influenced by the nature of Lewis acidic species present. Chapter eight describes the Stereoselective benzylic elaboration of (o-methoxybenzyl methyl ether)Cr(CO)3 achieved via selective removal of the exo benzylic proton from transition states with the methoxy groups anti to each other.